Clinton cash the untold story of how and why foreign governments and businesses helped make Bill and Hillary rich - Schweizer, Peter (New York Harper, 2015)
In 2000, Bill and Hillary Clinton owed millions of dollars in legal debt. Since then, they?ve earned over
Includes bibliographical references (pages 187-243).
Keywords: Clinton, Bill, 1946---Finance, Personal